1999
DOI: 10.1002/hep.510290320
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor increases mitochondrial oxidant production and induces expression of uncoupling protein-2 in the regenerating rat liver

Abstract: The growth-stimulatory actions of tumor necrosis factor ␣ (TNF-␣) after partial hepatectomy (PH) are difficult to reconcile with its well-established role in the genesis of liver injury. The lethal actions of TNF are thought to involve the induction of oxidant production by mitochondria. It is not known if TNF initiates mitochondrial oxidant production after PH. Furthermore, if this potentially toxic response follows PH, it is not clear how hepatocytes defend themselves sufficiently so that replication, rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
2
5

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(142 citation statements)
references
References 73 publications
(113 reference statements)
6
128
2
5
Order By: Relevance
“…These authors tested the hypothesis that tumour necrosis factor-α increases mitochondrial oxidant production after partial hepatectomy. They observed that the tumour necrosis factor-α-dependent increase in oxidant production by liver mitochondria promoted UCP2 induction, which may represent an antioxidant defence mechanism [122]. The same authors observed an increased level of UCP2 in hepatocytes cultured in the presence of lipid emulsion [126].…”
Section: Regulation Of Reactive Oxygen Species (Ros)mentioning
confidence: 93%
See 2 more Smart Citations
“…These authors tested the hypothesis that tumour necrosis factor-α increases mitochondrial oxidant production after partial hepatectomy. They observed that the tumour necrosis factor-α-dependent increase in oxidant production by liver mitochondria promoted UCP2 induction, which may represent an antioxidant defence mechanism [122]. The same authors observed an increased level of UCP2 in hepatocytes cultured in the presence of lipid emulsion [126].…”
Section: Regulation Of Reactive Oxygen Species (Ros)mentioning
confidence: 93%
“…ROS are also produced in the destruction of cells during infection, in the degradation of fatty acids and other molecules by peroxisomes, and as byproducts of processes that defend against toxic chemicals [121]. Excess superoxide ions may cause peroxidation of phospholipids, damage mitochondrial DNA, alter proteins or induce transcriptional factors [122]. Oxygen radicals can damage DNA, phospholipids and proteins, and also affect the transcription of genes.…”
Section: Regulation Of Reactive Oxygen Species (Ros)mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibiting BAT UCP-1 or disruption of UCP-2 gene in mice stimulates ROS production, while both the ROS-inducing agent tertbutyl hydroperoxide (TBHP) and tumour necrosis factor-a (TNFa) can induce hepatocyte UCP-2 mRNA; this suggests that UCPs may also serve as an antioxidant defence mechanism (Negre-Salvayre et al, 1997;Cortez-Pinto et al, 1999;Lee et al, 1999;Arsenijevic et al, 2000). Perhaps consistent with this is the observation that fatty livers from ob/ob mice or ethanol-fed lean mice show up-regulation of hepatic transcripts for UCP-2, while hepatocyte death is not increased (Rashid et al, 1999).…”
Section: Experimental Therapeuticsmentioning
confidence: 99%
“…24,25 UCP2 has wide tissue distribution, but in normal liver it has been localized mainly to Kupffer cells. 26 Increased hepatic UCP2 mRNA levels were found after partial hepatectomy, 27 although the cell-specific localization and functional significance of this phenomenon is unclear. It has been suggested that UCP2 may be protective by limiting ROS production in livers exposed to excess fuel supply (e.g., in fatty liver), although the increased presence of UCP2 in these conditions is believed to compromise ATP synthesis at the same time, and genetic ablation of the UCP2 gene in ob/ob mice actually results in no obvious long-term effects on liver steatosis.…”
mentioning
confidence: 99%